Asymptomatic young man with an incidental murmur. Issue 15 (31st May 2018) - Shojaeifard, Maryam; Pouraliakbar, Hamid Reza; Houshmand, Golnaz
Abstract : Clinical introduction: A 32-year old man was referred to our institution for transthoracic echocardiography (TTE) following detection of an incidental murmur on physical examination before blood donation. He was asymptomatic with no significant medical history. Physical examination revealed dual heart sounds with a grade II/VI systolic murmur heard in the left sternal border. An ECG was in normal sinus rhythm. TTE was performed (figure 1A–C, online supplementary videos 1–4 ) followed by cardiac CT angiography (CTA) (figure 1D, E ). Question: What is the diagnosis? Pericardial cyst. Ventricular septal defect. Kawasaki. Anomalous left coronary artery from pulmonary artery (ALCAPA).